Pengaruh Strategi Pembelajaran Teka-Teki Silang Terhadap Hasil Belajar Peserta Didik Madrasah Ibtidaiyah - Akhmad Fauzi; Masrurotul Maghfiroh; Muhammad Husnur Rofiq (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Teaching using learning strategies is very necessary for improving student learning outcomes during the learning process. Educators must choose strategies that can attract the interest of students so that they are not boring and monotonous and so that students will be more active in the learning process. One of them is the crossword puzzle learning strategy, students can play without losing the essence of learning, more enthusiastic, enthusiastic in following learning. This study aims to determine the implementation and influence of crossword Puzzle learning strategies on the learning outcomes of grade III students in theme 6 subtheme 1 at MI Islamiyah Sidoarjo. This type of research is quantitative Quasi Experiment using Non-equivalent control group design. With a class III research sample of 70 students. Descriptive analysis on the experimental class post-test data was 81.56 while the control class was 72.15, the average score of students in the class was better than in the control class Similarly, the independent sample t-test obtained sig scores. (2-tailed) 0.007 < 0.05 so it can be concluded that there is a difference in the average learning outcomes of students between the experimental class and the control class.